2014
DOI: 10.2298/gensr1402515k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of citrullinaemia carrier and detection of a new silent mutation at 240bp position in ASS1 gene of normal Holstein cattle

Abstract: The autosomal recessive genetic disorders are regularly investigated especially in Indian Holstein and Holstein Crossbred bulls before they entered in semen collection so that a defective gene should not be transmitted to future generations. Bovine citrullinaemia first reported in Australia is a metabolic disorder as one of the enzymes, Argininosuccinate synthetase (ASS) involved in urea cycle is impaired in function. The mutation responsible for citrullinemia has been characterized as a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similarly, Ramesha et al (2017) screened Indian native cattle and buffalo populations and reported no citrullinemia carriers among the studied animals. In a study carried out in India, Kotikalapudi et al (2014) identified a carrier bull among the Indian Holstein population. They also reported a novel polymorphism within exon 3 of ASS1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ramesha et al (2017) screened Indian native cattle and buffalo populations and reported no citrullinemia carriers among the studied animals. In a study carried out in India, Kotikalapudi et al (2014) identified a carrier bull among the Indian Holstein population. They also reported a novel polymorphism within exon 3 of ASS1 gene.…”
Section: Discussionmentioning
confidence: 99%